2023
DOI: 10.3390/biom13071043
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Transport Properties of RONS across Nitro-Oxidized Membranes

Davronjon Abduvokhidov,
Maksudbek Yusupov,
Aamir Shahzad
et al.

Abstract: The potential of cold atmospheric plasma (CAP) in biomedical applications has received significant interest, due to its ability to generate reactive oxygen and nitrogen species (RONS). Upon exposure to living cells, CAP triggers alterations in various cellular components, such as the cell membrane. However, the permeation of RONS across nitrated and oxidized membranes remains understudied. To address this gap, we conducted molecular dynamics simulations, to investigate the permeation capabilities of RONS acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…When compared with other studies on the hydroperoxidation of 50% POPC, the nitrated membrane demonstrated similar permeability for hydrophilic species but greater permeability than non-oxidized and hydroperoxidized POPC for hydrophobic species. In a recent MD study, Abduvokhidov et al investigated the transport properties of RONS across membranes with varying degrees of lipid nitro-oxidation [ 185 ]. The results, obtained using US simulations, revealed that certain RONS, namely • NO, • NO 2 , N 2 O 4 , and O 3 , exhibited higher penetration capabilities across both native and nitro-oxidized membranes compared to HNO 3 , s-cis -HONO, s-trans -HONO, H 2 O 2 , HOO • , and • OH.…”
Section: Non-reactive MD Simulations Of Lipid Membranesmentioning
confidence: 99%
“…When compared with other studies on the hydroperoxidation of 50% POPC, the nitrated membrane demonstrated similar permeability for hydrophilic species but greater permeability than non-oxidized and hydroperoxidized POPC for hydrophobic species. In a recent MD study, Abduvokhidov et al investigated the transport properties of RONS across membranes with varying degrees of lipid nitro-oxidation [ 185 ]. The results, obtained using US simulations, revealed that certain RONS, namely • NO, • NO 2 , N 2 O 4 , and O 3 , exhibited higher penetration capabilities across both native and nitro-oxidized membranes compared to HNO 3 , s-cis -HONO, s-trans -HONO, H 2 O 2 , HOO • , and • OH.…”
Section: Non-reactive MD Simulations Of Lipid Membranesmentioning
confidence: 99%
“…Surrounding this lipid bilayer are two distinct water phases, one on the top and next on the bottom, each containing 6250 water molecules (for a total of 12 500 water molecules). Diverse model systems were created by altering lipid compositions, specifically 10%, 20%, 30%, and 40% of nitrated DOPC (DOPC-NIT) and native DOPC (1,2-dioleoyl-sn-glycero-3-phosphocholine), as depicted in figure 1(b) (see table 1) [44].…”
Section: Methodsmentioning
confidence: 99%
“…These oxidized products can then react with the cellular components too. In addition, it is also noticed that with CAP, the less hydrophilic species-specifically NO, NO 2 , N 2 O 4 , and O 3 -show greater permeability through lipid bilayers when compared to their hydrophilic counterparts, which include HNO 3 , s-cis-HONO, s-trans-HONO, H 2 O 2 , HO 2 , and OH [69]. In addition to the lipid bilayers, the RONS generated through the synergistic effect of CAP and PSMs can damage the nucleic acid of the DNA present inside the cell.…”
Section: Intercellular Damage Caused By Oxidative Stressmentioning
confidence: 98%